1979
DOI: 10.1021/i360069a007
|View full text |Cite
|
Sign up to set email alerts
|

Steam Cracking of Hydrocarbons. 1. Pyrolysis of Heptane

Abstract: Bajus, M.; Vesely, V.; Leclercq, P.A.; Rijks, J.A. Published in:Industrial and Engineering Chemistry. Product Research and Development DOI:10.1021%2Fi360069a007 10.1021/i360069a007Published: 01/01/1979 Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
73
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 14 publications
12
73
0
Order By: Relevance
“…Numerous studies have been published on the pyrolysis of n-paraffins such as ethane, propane, n-butane, n-heptane, n-decane, n-hexadecane etc. at atmospheric pressure [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The main thrust in these studies has been to enhance the yield of low molecular weight olefins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been published on the pyrolysis of n-paraffins such as ethane, propane, n-butane, n-heptane, n-decane, n-hexadecane etc. at atmospheric pressure [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The main thrust in these studies has been to enhance the yield of low molecular weight olefins.…”
Section: Introductionmentioning
confidence: 99%
“…Appleby et al [8], Murata and Saito [9,11], Bajus et al [12], Aribike and Susu [6] and Pant and Kunzru [13] have investigated the kinetics and product distribution of atmospheric pressure pyrolysis of n-heptane. Aribike and Susu [7] developed a detailed mechanistic model of n-heptane pyrolysis, whereas Pant and Kunzru [13] developed a model based on a molecular reaction scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 11 and 12 show the ratio of methane and ethane to ethene for both reactors at 780 "C in identical conditions. This property of the reaction system is not specific for methylcyclohexane, but is valid for other hydrocarbons too, e.g., heptane (Bajus et al, 1979), straight-run naphtha, and naphthas from catalytic reforming after the extraction of aromatic hydrocarbons (Bajus et al, 1977). The decrease in yields of methane and ethane is due probably to the scavenging of methyl and ethyl radicals, which together with hydrogen radicals belong to the most active and have an important place in the propagation of the radical chain.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…This indicates that the rate constant was independent of the conversion. Bajus et al (1979) and Aribike and Susu (1988a) have reported that fmt-order rate constants for nheptane pyrolysis are independent of conversions at other temperatures (residence time <0.06 s and V/F 4 . 0 s, respectively), thus confirming the assumption that the thermal cracking of nheptane can be represented by first-order kinetics.…”
Section: Mineral Materialsmentioning
confidence: 98%
“…In a tubular flow reactor there is no sharp difference between the preheater and the reactor section (Bajus et al, 1979;Taralas et al, 1991) was calculated by converting non-isothermal data to pseudoisothermal conditions by the equivalent reactor concept (Taralas et al, 1991 VR, is defined as the volume necessary to reach the same conversion of the hydrocarbon at a constant reference temperature TRI as under the non-ideal isotherm conditions of the experiments with the temperature T, thus:…”
Section: Mineral Materialsmentioning
confidence: 99%